Dynamic monitoring of cognitive impairment and prognostic recurrence in patients with stroke by serum HDAC3 and FOXO1: a new diagnostic method - Li, Xintong; Wang, Lulu; Xiao, Bin; Liu, Zhengkun; Dou, Yue (Journal of Medical Biochemistry, 2025)
Objective: To evaluate the clinical value of dynamically monitoring serum histone deacetylase 3 (HDAC3) and forkhead box protein O1 (FOXO1) levels in evaluating cognitive impairment (CI) in cerebral stroke (CS) patients, so as to facilitate early identification of high-risk individuals and guide targeted interventions. Methods: This study included 120 CS patients admitted from March, 2023 to March, 2024, with their serum HDAC3 and FOXO1 levels examined upon admission (T0) and at 2 (T1) and 24 hours (T2) following treatment. Differences in biomarker levels (CI group vs. non-CI group) were analyzed, and the predictive value of HDAC3 and FOXO1 for CI was determined. In addition, patients were followed up for 1 year prognosis, and the predictive effect of HDAC3 and FOXO1 on the prognostic recurrence of CS was analyzed. Results: CI occurred in 46 cases. HDAC3 expression was markedly increased in CI cases versus non-CI patients at T0, T1, and T2, whereas FOXO1 differed significantly only at T1 and T2 (P<0.05). HDAC3 and FOXO1 showed maximal predictive value for CI at the T2 timepoint. Similarly, the increase of HDAC3 and FOXO1 was also related to the risk of prognosis recurrence of CS patients. The sensitivity and specificity of combined detection of HDAC3 and FOXO1 in predicting the prognosis recurrence of CS patients were 84.38% and 78.41% (P<0.05). Conclusion: The pattern of dynamic HDAC3 and FOXO1 changes provides a new diagnostic scheme for the development of CI and prognostic recurrence in CS patients.